Hubungan Antara Hasil Seleksi Penerimaan Mahasiswa Baru ( Sipenmaru ) Motivasi Belajar dan Dukungan Keluarga Dengan Prestasi Belajar Mahasiswa Di Akademi Keperawatan PPNI Surakarta - Joko Waluyo, Sunaryo; -, Sugiyarto (Politeknik Insan Husada Surakarta, 2015)
Background: quality health services, to be supported by qualified health personnel, quality health indicators one of which is the achievement of academic achievement. Implementation Sipenmaru standards that have been set, motivation and family support affect the achievement of student learning. Methods: This study is a descriptive correlational cross-sectional study design. Sampling technique with random sampling sample of 75 students AKPER PPNI Semester IV. Primary data on, motivation, family support and students' learning is obtained from the questionnaires, data Sipenmaru of documentation and data values Sipenmaru results obtained from the learning achievement evaluation throught ests mid semester IV. Results: The results of the multiple correlation analys is of the independent variable values Sipenmaru (X1), motivation (X2) and family support (X3) on the dependent variable learning achievement (Y) obtained results R (correlation coefficient) 0.916, multiple regression test results obtained values F count=124.046 and F table =3124 and a significance value of 0000, F (124.046) > F table(3124) and Sig.0.000<0.05. Effective contribution (R2) /R Square : 0.840 jointly acquired. Conclusion: There is a strong positive relationshipand significant correlation between interest and motivation toward achievement of students in Nursing Academy PPNI Surakarta. Keywords: Sipenmaru, Motivation, Family support,Learning Achievement